Genetic diversity among fourteen different Fusarium species using RAPD marker - SHITAL R. BONDE; ANIKET K. GADE; MAHENDRA K. RAI (Society for Indonesian Biodiversity, 2013)
Bonde SR, Gade AK, Rai MK. 2012. Genetic diversity among fourteen different Fusarium species using RAPD marker. Biodiversitas 14: 55-60. We report genetic diversity of total fourteen different Fusarium species by RAPD-PCR analysis using 25 random primers. The genus Fusarium is food borne pathogen responsible for T-2 toxin production which affects human and animal health. In the present study, total 14-different species of Fusarium were analyzed on the basis of genetic diversity using RAPD method. A dendrogram was developed by UPGMA method. RAPD analysis was carried out by using 25 different universal primers each of them consisted of 10 bases. Genetic similarity coefficients between pair wise varied from 0.00 to 0.9 based on an unweighted paired group method of arithmetic average (PGMA) cluster analysis. RAPD-PCR technique can be used as an important tool for the genetic differentiation Fusarium species.